Nowhere to Remember : Hanford, White Bluffs, and Richland to 1943 - Franklin, Robert, 1981-; Bauman, Robert, 1964- (Book collections on Project MUSE., 2018)
"Based on oral histories, this volume examines the small towns of Hanford, White Bluffs, and Richland, Washington, before the federal government seized the land and set up one of the secret locations of the Manhattan Project, which came to be know simply as "Hanford.""--Provided by publisher.